Exploring the Link Between Cashless Society and Cybercrime in Indonesia - Mauladi, Kemal Farouq; Jaya, I Made Laut Mertha; Esquivias, Miguel Angel (Journal of Telecommunications and the Digital Economy, 2022)
This study examines whether the rise in cybercrime activity in Indonesia is associated with the perceived benefits, convenience, and risk of a cashless society. In doing so, we apply Structural Equation Modelling (SEM) to a total sample of 200 Indonesian respondents who have been victims of cyber fraud. The results indicate that the high cybercrime rate, including phishing, distributed denial-of-service (DDoS), and social engineering, is positively associated with the perceived benefits and risks of transacting online. The rise in cases of DDoS can particularly be linked to consumers’ increasing perceptions of convenience in undertaking cashless transactions. The findings suggest that more stringent cyber law enforcement needs to be implemented. Digital technologies will continue to improve, and more consumers will do transactions digitally. With increasing volumes of cashless transactions, the risk of cyber attacks will likely increase. Stakeholders need to strengthen data privacy and provide a secure environment for customers. International cooperation should be promoted through the establishment of virtual world law as economic activities and cybercrime risks now become borderless.